ASSESMEN KINERJA BERBASIS MASALAH PADA MODEL PEMBELAJARAN TEAM ASISTED INDIVIDUALIZATION (TAI) - ROETH A.O. NAJOAN (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The study examined the effects of instructional Team Assisted Individualization (TAI) models and assessment performance based on problems on the elementary school students’ previous knowledge on Mathematics by controlling the first students’ competency. The method of the study was experimental method with factorial design 2 x 2. The population was 128 students in Grade 4 in Elementary School Students in Tomohon City. The findings showed that: there was an interaction effect between assessment performances based on problems and instructional TAI models after controlling the students’ previous knowledge. The result of the students’ achievement in which the students were given the assessment problems solving by using TAI was higher than the result of the classical instructional models, after controlling the students’ previous knowledge. The result of the students in which the students applied group classical instructional models was higher than the students with assessment performance problem solving after controlling the students previous.